Performance of hollow fiber supported liquid membrane on the extraction of mercury(II) ions - Uedee, Ekapong; Ramakul, Prakorn; Pancharoen, Ura; Lothongkum, Anchaleeporn W. (My University, 2008)
The extraction and recovery or stripping of mercury ions from chloride media using microporous hydrophobic hollow fiber supported liquid membranes (HFSLM) has been studied. Tri-n-octylamine (TOA) dissolved in kerosene was used as an extractant. Sodium hydroxide was used as a stripping solution. The transport system was studied as a function of several variables: the concentration of hydrochloric acid in the feed solution, the concentration of TOA in the liquid membrane, the concentration of sodium hydroxide in the stripping solution, the concentration of mercury ions in the feed solution and the flow rates of both feed and stripping solutions. The results indicated that the maximum percentages of the extraction and recovery of mercury ions of 100% and 97% were achieved at the concentration of hydrochloric acid in the feed solution of 0.1 mol/l, the concentration of TOA at 3% v/v, the concentration of sodium hydroxide at 0.5 mol/l and the flow rates of the feed and stripping solutions of 100 ml/min. However, the concentration of mercury ions from 1-100 ppm in the feed solution had no effect on the percentages of extraction and recovery of mercury ions. Thus, these results have identified that the hollow fiber supported liquid membrane process has high efficiency on both the extraction and recovery of mercury (II) ions. Moreover, the mass transfer coefficients of the aqueous phase (k i ) and membrane or organic phase (k m ) were calculated. The mass transfer coefficients of the aqueous phase and organic phase are 0.42 and 1.67 cm/s, respectively. The mass transfer coefficient of the organic phase is higher than that of the aqueous phase. Therefore, the mass transfer controlling step is the diffusion of the mercury ions through the film layer between the feed solution and the liquid membrane. © 2008 Springer.
Keywords: Extraction; Hollow fiber; Liquid Membrane; Mass transfer; Mercury